2016
DOI: 10.5115/acb.2016.49.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Descent of mesonephric duct to the final position of the vas deferens in human embryo and fetus

Abstract: Because the ureter arises from the mesonephric or Wolffian duct (WD), the WD opening should migrate inferiorly along the urogenital sinus or future urethra. However, this process of descent has not been evaluated morphometrically in previous studies and we know little about intermediate morphologies for the descent. In the present work, serial sagittal sections of 15 specimens at gestational age 6–12 weeks and serial horizontal sections of 20 specimens at 6–10 weeks were analyzed. Monitoring of horizontal sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They postulated that this could be resultant from hypertrophy induced by transient urethral obstruction distal to the bladder neck and hormone influenced (testosterone) dependent growth [ 34 ]. Important in both male and female fetuses, Jin et al found that SM differentiation in the bladder and urethra is crucial for the Wolffian duct orifice descent [ 46 ].…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…They postulated that this could be resultant from hypertrophy induced by transient urethral obstruction distal to the bladder neck and hormone influenced (testosterone) dependent growth [ 34 ]. Important in both male and female fetuses, Jin et al found that SM differentiation in the bladder and urethra is crucial for the Wolffian duct orifice descent [ 46 ].…”
Section: Cell Populations In or Associated With The Lutmentioning
confidence: 99%
“…2 a). The result is an opening of the ureteric buds in this posterior surface which is almost that of their initial implantation site, while the WD orifices descend to the future prostatic urethra (Jin et al 2016 ). The cephalic region of the WD gives rise to the epididymal duct (Domeniconi et al 2016 ) that occupy the body and tail of the epididymis, and to the median region to the VD (Fig.…”
Section: Introductionmentioning
confidence: 99%